Improved mapping of ksgB and integration of transposons near relB and terC in Escherichia coli. - Diderichsen, B (1981)
Tn5 transposons were integrated near relB at 34.2 min. ksgB was mapped at 36.4 min, 2 min from its previously assumed position.